1998
DOI: 10.1126/science.279.5349.389
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Restriction of AIDS Pathogenesis by an SDF-1 Chemokine Gene Variant

Abstract: Stromal-derived factor (SDF-1) is the principal ligand for CXCR4, a coreceptor with CD4 for T lymphocyte cell line-tropic human immunodeficiency virus-type 1 (HIV-1). A common polymorphism, SDF1-3'A, was identified in an evolutionarily conserved segment of the 3' untranslated region of the SDF-1 structural gene transcript. In the homozygous state, SDF1-3'A/3'A delays the onset of acquired immunodeficiency syndrome (AIDS), according to a genetic association analysis of 2857 patients enrolled in five AIDS cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
412
9
6

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 655 publications
(446 citation statements)
references
References 42 publications
19
412
9
6
Order By: Relevance
“…Gene or allele frequency is the occurrence of an allele in a population in relation to all alleles of that gene on the same locus expressed as a fraction. Overall gene frequencies of our analyzed population of CCR2-64I (10.6%; n Ω 206), CCR5D32 (7.6%; n Ω 118), and SDF1-3ƒA (18.9%; n Ω 203) were similar than those seen in populations previously reported (2,3). Forty (19%) and 16 (13.5%) patients were heterozygous, while two patients and one patient were homozygous for CCR2-64I and CCR5D32, respectively.…”
Section: Patient Population and Genotype Distributionsupporting
confidence: 72%
See 1 more Smart Citation
“…Gene or allele frequency is the occurrence of an allele in a population in relation to all alleles of that gene on the same locus expressed as a fraction. Overall gene frequencies of our analyzed population of CCR2-64I (10.6%; n Ω 206), CCR5D32 (7.6%; n Ω 118), and SDF1-3ƒA (18.9%; n Ω 203) were similar than those seen in populations previously reported (2,3). Forty (19%) and 16 (13.5%) patients were heterozygous, while two patients and one patient were homozygous for CCR2-64I and CCR5D32, respectively.…”
Section: Patient Population and Genotype Distributionsupporting
confidence: 72%
“…To assess the effects of polymorphisms on graft survival, only first hepatic transplants were analyzed. The oligonucleotide primers for SDF1-3ƒA, CCR2-64I and CCR5D32 were used as previously published (2,3,18). PCR products were digested with 5 U MspI at 37 aeC (SDF1-3ƒA wild-type), or BsaBI at 60 aeC (CCR2-64I mutation) (New England Biolabs, MA, USA).…”
Section: Patient Demographicsmentioning
confidence: 99%
“…Carriers of the A allele in the SDF-1 gene were at increased risk of developing ICA occlusive disease compared with individuals homozygous for the G. The -801A variant of the SDF-1 gene has been associated with genetic restriction of AIDS pathogenesis, as well as with enhanced CD34+ progenitor cell mobilisation from bone marrow [29,30]. Soriano et al have shown an association between high plasma SDF-1 levels and the SDF-1 A allele [31].…”
Section: Discussionmentioning
confidence: 99%
“…Total DNA was extracted from PBMC using a Q1 Amp Blood Kit (QIAGEN, CA) and genotyping was carried out by PCR/RFLP assays as described earlier by Winkler et al [28]. Standard PCR conditions and primers namely for CCR-64I Fwd: 5 0 -CTCGG ATCTTGTGGG-CAACATGATGG-3 0 , Rev: 5 0 -CTGTGAATA A-TTTGCACATTGC-3 0 ; SDF1-3 0 A Fwd: 5 0 -GACCAGTCAACCTGGGCAAA-3 0 , Rev: 5 0 -CACAT-GATGATGGATGAGACAGAGAA-3 0 and; MCP-1-2518-G/A Fwd: 5 0 -TCA CGCCAGCACTGAC-3 0 , Rev: 5 0 -ACTTCAGGAAGGAGTTGT-3 0 were used in a PTC 200 system and PCR amplified products were digested with restriction endonuclease (BsaBI, MspI and PvuII respectively) for 3 h and then separated in 2.0 % agarose-gel electrophoresis [1,28].…”
Section: Genotypingmentioning
confidence: 99%
“…A G to A substitution at position 801 in the 3 0 untranslated region (UTR) of the SDF1 gene (SDF1-3 0 A) has been reported to slow disease progression [28] although in subsequent studies this claim has been refuted [7,14].…”
Section: Introductionmentioning
confidence: 99%